Activity Prediction of Bioactive Compounds Contained in Etlingera elatior Against the SARS-CoV-2 Main Protease: An In Silico Approach - Dwi Syah Fitra Ramadhan; Taufik Muhammad Fakih; Arfan Arfan (Borneo Journal of Pharmacy, 2020)
The COVID-19 pandemic has become a serious problem today, with its prevalence increasing every day. The SARS-CoV-2 main protease (MPro) is a promising therapeutic target to inhibit replicating and spreading the virus that causes COVID-19. The compounds contained in the Etlingera elatior plant has the potential. This study aimed to examine the compounds' activity in E. elatior against SARS-CoV-2 MPro using in silico methods. A total of seven compounds contained in E. elatior were obtained from the Knapsack database. The compounds were then docked into the SARS-CoV-2 MPro receptor's active site with the PDB ID 6LU7. Afterward, the biological activities were predicted by the PASS prediction webserver. The molecular docking results showed that ergosterol peroxide and sitostenone had the best binding energy with -10.40 kcal/mol and -9.17 kcal/mol, respectively. The in silico PASS prediction showed it has potential as antiviral therapy. It concluded ergosterol peroxide and sitostenone has the potential as SARS-CoV-2 MPro inhibitor candidate.